2018
DOI: 10.1590/1516-3180.2017.0177141217
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of non-dialysis chronic kidney disease patients: the PROGREDIR study. A cross-sectional study

Abstract: We identified low energy and high protein intake in this population. Protein intake was inversely related to eGFR. Dietary patterns were associated with age, gender, schooling level, hypertension and diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
2
10
0
6
Order By: Relevance
“…Two dietary patterns, labeled Unhealthy and Healthy, were identified in the whole group. In a previous study comprising Brazilian nondialyzed patients with CKD stages 3 and 4 ( n = 454), three dietary patterns were found: snack pattern (breads, biscuits, cakes, farinaceous products, butter, margarine, eggs, processed meat, sweets, snacks, whole dairy products, and sweetened beverages); mixed pattern , consisting of healthy foods but with red meat (whole grains, pasta, tubers, red meat, poultry, fish, seafood, fruits, vegetables, low-fat dairy products, and natural juice); and traditional pattern (white rice, beans, and coffee) [34]. The findings from the present study and our previous study underline the diversity of food patterns in CKD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two dietary patterns, labeled Unhealthy and Healthy, were identified in the whole group. In a previous study comprising Brazilian nondialyzed patients with CKD stages 3 and 4 ( n = 454), three dietary patterns were found: snack pattern (breads, biscuits, cakes, farinaceous products, butter, margarine, eggs, processed meat, sweets, snacks, whole dairy products, and sweetened beverages); mixed pattern , consisting of healthy foods but with red meat (whole grains, pasta, tubers, red meat, poultry, fish, seafood, fruits, vegetables, low-fat dairy products, and natural juice); and traditional pattern (white rice, beans, and coffee) [34]. The findings from the present study and our previous study underline the diversity of food patterns in CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The findings from the present study and our previous study underline the diversity of food patterns in CKD patients. Of note, Machado et al [34] also demonstrated that gender, school degree, and comorbidities, such as diabetes and hypertension, influenced dietary patterns. The latter findings are in accordance with those reported in our previous study—based on the same Brazilian NHS survey—in which the sociodemographic and geographical variables were found to influence the food consumption frequency in CKD patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…The Reasons for Geographic and Racial Differences in Stroke study conducted for CKD populations in the Southeastern United States, identified a "Southern" dietary pattern characterized by fried foods, organ meats, and sweetened beverages, which is typical of Southern cuisine 33 . Similarly, the PROGREDIR study conducted among pre-dialysis CKD patients in São Paulo, Brazil identified a "traditional" dietary pattern (composed of white rice, beans, and coffee) typical to the local community 34 . www.nature.com/scientificreports/ In this study, we did not observe any significant association between serum phosphorus level and any individual nutrient, including dietary phosphate.…”
Section: Discussionmentioning
confidence: 99%
“…Macro- and micronutrient intakes were adjusted for energy intake using the residual method [ 33 ]. Detailed nutritional data of the cohort has been published elsewhere [ 34 ].…”
Section: Methodsmentioning
confidence: 99%